The importance of global warming and public health legislation (One Health & Risk Management, 2021)
Introduction. The law is a legal tool of protection and trust of any sovereign country. The concept of health is regarded as a value without which man could not evolve. The environment directly affects our lifestyle and obviously our health. Different problems have arisen due to human negligence, the worst being the health-related ones. The increasing population and the material consumption have resulted into a strong negative impact on the environment. The excessive consumption of natural resources has led to an increase in greenhouse gas emissions, causing global warming over the last century and, ultimately, to global climate deregulation.This phenomenon poses great threats on the environment, economic growth and global prosperity. The Republic of Moldova is no exception. Nowadays, global warming has a powerful impact on human health, thus the implementation and compliance to policies and regulations act as a link between population health and climate change. This issue should be addressed at the highest level of the country. The purpose of this research was to review health policies.Material and methods. A descriptive research design was carried out on data obtained from the document analysis in health policy: laws, government decisions, orders, provisions and other normative acts retrieved from the websites of the Ministry of Health, Labour and Social Protection of the Republic of Moldova. 250 legislative documents were studied. The data reviewed on medical legislation was introduced within a table, having the following aspects studied: the global warming impact, the environment, overall health and hygiene measures. 27 bibliographic sources from Romania, Great Britain, Belgium, Poland, Czech Republic, and Ireland were analysed to justify the study of policy documents.Results. Global warming is a current issue that must be considered at the highest level within a state viz. the law. Unfortunately, the issue of global warming and its impact on health is underestimated in our country, the Republic of Moldova. The development and implementation of the laws and legislative documents on the impact of global warming on health has been very poorly researched. Of the large number of laws and regulations enacted each year, very few are related to global warming and its negative health effects.Based on the analysis of 29 laws, 3 of them indicated negative factors affecting the environment; out of 84 government decisions, there were identified restrictions regarding the environment and health; out of 200 orders, 10 orders stated the importance of environmental protection and measures to be undertaken.Conclusions. The proper functioning of the legislature is the key solution in preventing health-related conditions, maintaining health and well-being among population, avoiding complications, promoting a healthy lifestyle in case humans are being affected by multiple factors, including the impact of climate change on the public health.